Prove that.
I think the answer won't come 1.
![Prove thatI think the answer wont come 1 class=](https://us-static.z-dn.net/files/db6/af8b964bb444d62283159c654d2b8cef.jpg)
Answer:
[tex]{ \rm{ \frac{ {4}^{a + 2} + {4}^{a} }{17 \times {4}^{a} } }} \\ \\ = { \rm{ \frac{( {4}^{a} \times {4}^{2} ) + {4}^{a} }{17 \times {4}^{a} } }} \\ \\ = { \rm{ \frac{ {4}^{a} }{ {4}^{a} } ( \frac{ {4}^{2} + 1}{17}) }} \\ \\ = { \rm{ \frac{ {4}^{2} + 1 }{17} }} \\ \\ = { \rm{ \frac{16 + 1}{17} }} \\ \\ { \rm{ = \frac{17}{17} }} \\ \\ = 1[/tex]
hence proved